Catalyst for catalytic oxidative degradation of VOCs in chemical tail gas and preparation method thereof

By multi-layer coating of precious metals, rare earth salts, mesoporous titanium dioxide and graphite, an efficient catalyst was prepared, which solved the problems of low catalytic activity and poor stability of existing catalysts when treating chemical exhaust VOCs, and achieved efficient VOCs degradation effect.

CN119588344APending Publication Date: 2025-03-11CHANGZHOU XINRI CATALYST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411773436.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When treating chemical exhaust VOCs, existing catalysts have problems such as high ignition temperature, low catalytic activity and poor stability, which are difficult to meet the requirements of chemical exhaust treatment.

Method used

A catalyst with a multi-layered coated structure was prepared by mixing precious metal solution, rare earth salt solution and mesoporous titanium dioxide, calcined, mixed with graphite, and impregnating on the substrate.

Benefits of technology

The catalytic activity and stability of the catalyst are improved, and the degradation capacity of chemical exhaust VOCs is enhanced. The degradation effect reaches more than 99.5%, meeting relevant emission standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170888650000111
    Figure BDA0005170888650000111
  • Figure BDA0005170888650000121
    Figure BDA0005170888650000121
Patent Text Reader

Abstract

The invention belongs to the technical field of volatile organic compounds, and particularly discloses a catalyst for catalytic oxidative degradation of chemical tail gas VOCs and a preparation method of the catalyst. The preparation method comprises the following steps: mixing a noble metal solution, a rare earth salt solution and mesoporous titanium dioxide, separating precipitates after mixing, and calcining to obtain a catalytic active component; then mixing and grinding the catalytic active component and graphite, and then dispersing into a solvent to obtain a mixed dispersion liquid; and dipping the substrate into the mixed dispersion liquid, and after dipping is completed, obtaining the catalyst for catalytic oxidation degradation of the VOCs in the chemical tail gas. The catalyst prepared by the invention has excellent stability and high catalytic activity, and can meet the treatment of chemical tail gas with high emission, high pollutant concentration and multiple pollutant types.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of volatile organic compound treatment, and in particular to a catalyst for catalytic oxidation degradation of chemical tail gas VOCs and a preparation method thereof. Background Art

[0002] VOCs, volatile organic compounds, refer to organic compounds that have high saturated vapor pressure, low boiling point, small molecular weight, and are easy to volatilize at room temperature under standard conditions. They are harmful to human health and environmental quality to a great extent. For example, many components in VOCs have been confirmed as carcinogens or mutagens, such as benzene and formaldehyde. Long-term exposure may increase the risk of cancer. It may also cause respiratory diseases and nervous system damage. For the environment, VOCs are one of the main sources of air pollution. They can produce harmful substances such as ozone and photochemical smog in the atmosphere, which have a serious impact on air quality; they also cause haze weather, which is closely related to VOCs discharged into the atmosphere. Therefore, the degradation of VOCs is of great significance.

[0003] There are many methods for treating VOCs, such as adsorption, thermal decomposition, biological treatment, and condensation collection, but catalytic combustion technology is generally practical, low-cost, and easy to promote and apply on a large scale. The core of catalytic combustion technology lies in the catalyst, which includes non-precious metal catalysts and precious metal catalysts. Non-precious metal catalysts have low cost and relatively good thermal stability, but low catalytic activity and high ignition temperature, making it difficult to achieve industrial application. Precious metal catalysts have unparalleled advantages over other metals, but their poor stability, high price, and resource shortage restrict their large-scale application.

[0004] Compared with VOCs produced by other sources, VOCs produced by chemical tail gas have some unique treatment difficulties. VOCs produced by chemical tail gas have the characteristics of multiple emission points, large emission volume, intermittent emission, unstable emission air volume, large changes in pollutant types and concentrations. This requires the catalyst to have a broad spectrum of catalytic activity and a high catalytic activity to cope with the problem of large emission volume.

[0005] Therefore, how to provide a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas and a preparation method thereof, and improve the catalytic activity, catalytic capacity and stability of precious metal catalysts are difficult problems to be solved urgently in this field. Summary of the invention

[0006] In view of this, the present invention provides a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas and a preparation method thereof, so as to solve the problem that the existing non-precious metal catalysts have high ignition temperature and are not suitable for treating VOCs in chemical tail gas. At the same time, it also solves the problem that traditional precious metal catalysts have poor stability and weak catalytic ability and cannot meet the requirements of chemical tail gas treatment.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas comprises the following steps:

[0009] 1) mixing a noble metal solution, a rare earth salt solution and mesoporous titanium dioxide, separating and calcining the precipitate after the mixing is completed to obtain a catalytically active component;

[0010] 2) mixing and grinding the catalytically active component and graphite, and then dispersing them in a solvent to obtain a mixed dispersion;

[0011] 3) The substrate is immersed in the mixed dispersion liquid for dipping, and after the dipping is completed, a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas is obtained.

[0012] Preferably, the mass ratio of the noble metal in the noble metal solution to the rare earth salt in the rare earth salt solution in step 1) is 1:3-5;

[0013] The noble metal in the noble metal solution includes one or more of a platinum compound, a palladium compound and a ruthenium compound;

[0014] The rare earth salt in the rare earth salt solution includes one or more of lanthanum salt, praseodymium salt, neodymium salt, cerium salt and yttrium salt.

[0015] Preferably, the mass concentration of the noble metal solution is 10-20%, and the mass concentration of the rare earth salt solution is 30-40%;

[0016] The mass ratio of the total volume of the noble metal solution and the rare earth salt solution to the mesoporous titanium dioxide is 30-50 mL: 1-3 g.

[0017] Preferably, the mixing time in step 1) is 4 to 6 hours;

[0018] In step 1), the calcination temperature is 200-400° C. and the calcination time is 1-2 hours.

[0019] Preferably, in step 2), the mass ratio of the catalytically active component to graphite is 1-5:0.5-2.

[0020] Preferably, the immersion time in step 3) is 10 to 12 hours.

[0021] Preferably, the substrate in step 3) comprises one or more of ceramic, cordierite, mullite, silicon carbide and stainless steel coated with a high temperature resistant oxide slurry.

[0022] Preferably, the high temperature resistant oxide slurry comprises one or more of an aluminum oxide aqueous solution, a magnesium oxide aqueous solution and a silicon oxide aqueous solution.

[0023] Another object of the present invention is to provide a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas prepared by the preparation method.

[0024] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The catalyst disclosed in the present invention is a multi-layer coated catalyst. The present invention first loads precious metal components and rare earth components through mesoporous titanium dioxide to form catalytically active components, and then uses a substrate to load the catalytically active components and graphite to achieve multi-layer coating of the precious metal components, thereby avoiding the consumption of precious metal components during use.

[0026] 2. The present invention uses mesoporous titanium dioxide to load the components with catalytic activity, which can not only effectively load and disperse the active components, but also play a role in spatially limiting and stabilizing the particles of the active components, reducing the problem of active component particles migrating, aggregating and growing under high temperature and high pressure treatment conditions, thereby affecting the catalytic activity. In addition, titanium dioxide also contributes to the catalytic decomposition of VOCs and can improve the catalytic activity of the catalyst.

[0027] 3. The present invention also adds graphite. Based on the electron-rich characteristics of graphite, it can activate the treated VOCs, reduce the potential barrier of the catalytic reaction, and improve the catalytic efficiency of the catalyst. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas, comprising the following steps:

[0029] 1) mixing a noble metal solution, a rare earth salt solution and mesoporous titanium dioxide, separating and calcining the precipitate after the mixing is completed to obtain a catalytically active component;

[0030] 2) mixing and grinding the catalytically active component and graphite, and then dispersing them in a solvent to obtain a mixed dispersion;

[0031] 3) The substrate is immersed in the mixed dispersion liquid for dipping, and after the dipping is completed, a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas is obtained.

[0032] In the present invention, the mass ratio of the noble metal in the noble metal solution to the rare earth salt in the rare earth salt solution in step 1) is 1:3-5, preferably 1:3.5-4.5, and more preferably 1:4.

[0033] In the present invention, the noble metal in the noble metal solution in step 1) includes one or more of platinum compounds, palladium compounds and ruthenium compounds.

[0034] In the present invention, the platinum compound includes one or more of platinum nitrate, platinum sulfite and tetranitroplatinic acid; the palladium compound includes one or more of palladium chloride, palladium nitrate and dichlorotetraamminepalladium.

[0035] In the present invention, the rare earth salt in the rare earth salt solution in step 1) includes one or more of lanthanum salt, praseodymium salt, neodymium salt, cerium salt and yttrium salt.

[0036] In the present invention, the mass concentration of the precious metal solution in step 1) is 10-20%, specifically 12%, 14%, 15%, 16%, and 18%; the mass concentration of the rare earth salt solution is 30-40%, specifically 32%, 34%, 35%, 36%, and 38%.

[0037] In the present invention, the mass ratio of the total volume of the noble metal solution and the rare earth salt solution to the mesoporous titanium dioxide in step 1) is 30-50 mL: 1-3 g, preferably 35-45 mL: 1.5-2.5 g, and more preferably 40 mL: 2 g.

[0038] In the present invention, the mixing time in step 1) is 4 to 6 hours, specifically 4.2 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.8 hours, 5 hours, 5.2 hours, 5.4 hours, 5.5 hours, 5.6 hours, and 5.8 hours.

[0039] In the present invention, the calcination temperature in step 1) is 200-400°C, specifically 220°C, 250°C, 280°C, 300°C, 320°C, 350°C, 360°C, 380°C; the calcination time is 1-2h, specifically 1.2h, 1.4h, 1.5h, 1.6h, 1.8h.

[0040] In the present invention, the mass ratio of the catalytically active component to graphite in step 2) is 1-5:0.5-2, preferably 2-4:0.8-1.5, and more preferably 3:1.

[0041] In the present invention, the solvent in step 2) is preferably water.

[0042] In the present invention, the immersion time in step 3) is 10 to 12 hours, specifically 10.2 hours, 10.5 hours, 11 hours, 11.5 hours, or 11.8 hours.

[0043] In the present invention, the substrate in step 3) comprises one or more of ceramic, cordierite, mullite, silicon carbide and stainless steel coated with a high temperature resistant oxide slurry.

[0044] In the present invention, the high temperature resistant oxide slurry comprises one or more of an aluminum oxide aqueous solution, a magnesium oxide aqueous solution and a silicon oxide aqueous solution.

[0045] In the present invention, the preparation method of the substrate is as follows:

[0046] The high temperature resistant oxide slurry is coated on ceramic, cordierite, mullite, silicon carbide or stainless steel, and then dried and calcined in sequence to obtain a substrate.

[0047] Specifically, 200 g of aluminum oxide, 100 g of magnesium oxide and 3 L of water are mixed and ground for 24 h to a particle size of D50 = 10 μm to obtain a high temperature resistant oxide slurry, and the high temperature resistant oxide slurry is coated on a cordierite substrate. The loading amount of the high temperature resistant oxide on the honeycomb ceramic is 100 g / m 3 , use compressed air to blow off the excess slurry, place the coated cordierite substrate at 110°C for 4 hours, and then calcine at 500°C for 10 hours to obtain the substrate material. The substrate materials used in this embodiment are all prepared with reference to this method, but this is not considered to be a limitation of the present invention.

[0048] The present invention also provides a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas prepared by the preparation method.

[0049] In the present invention, the loading amount of the catalytic active component in the catalyst for catalytic oxidation degradation of chemical tail gas VOCs is 0.5 to 8 g / m 3 , specifically 0.8g / m 3 , 1g / m 3 , 1.2g / m 3 , 1.5g / m 3 , 1.8g / m 3 , 2g / m 3 , 2.2g / m 3 , 2.5g / m 3 , 2.8g / m 3 , 3g / m 3 3.2g / m 3 3.5g / m 3 , 4g / m 3 4.5g / m 3 , 5g / m3 5.5g / m 3 , 6g / m 3 , 6.5g / m 3 , 7g / m 3 , 7.5g / m 3 .

[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] Example 1

[0052] Platinum nitrate with a mass concentration of 15% and lanthanum nitrate with a mass concentration of 30% were mixed (the mass ratio of platinum nitrate to lanthanum nitrate was 1:4) to obtain 500 mL of a mixed solution, and then 20 g of mesoporous titanium dioxide (JK-11-001-100) was added to the mixed solution, and stirring was started at 400 rpm. After stirring for 5 hours, the mixed solution was centrifuged and precipitated, and then the obtained precipitate was dried and calcined, and calcined at 300° C. for 1.5 hours to obtain a catalytically active component;

[0053] The catalytic active component obtained above was fully ground and mixed with graphite in a mass ratio of 5:1, and then the mixture was dispersed in water, and then the prepared cordierite substrate coated with the high temperature resistant oxide slurry was immersed in the dispersion for 10 hours, and dried after the immersion was completed to obtain a catalyst for catalytic oxidation degradation of chemical tail gas VOCs (the catalytic active component loading was 3.2 g / m 3 ).

[0054] Example 2

[0055] A palladium chloride solution with a mass concentration of 20% and a lanthanum nitrate solution with a mass concentration of 35% were mixed (the mass ratio of palladium chloride to lanthanum nitrate was 1:3) to obtain 500 mL of a mixed solution, and then 25 g of mesoporous titanium dioxide (JK-11-001-100) was added to the mixed solution, and stirring was started at 400 rpm. After stirring for 4 hours, the mixed solution was centrifuged and precipitated, and then the obtained precipitate was dried and calcined, and calcined at 250° C. for 2 hours to obtain a catalytically active component;

[0056] The catalytic active component obtained above was fully ground and mixed with graphite in a mass ratio of 2:1, and then the mixture was dispersed in water, and then the prepared cordierite substrate coated with the high temperature resistant oxide slurry was immersed in the dispersion for 10 hours, and dried after the immersion was completed to obtain a catalyst for catalytic oxidation degradation of chemical tail gas VOCs (the catalytic active component loading was 2.2 g / m 3 ).

[0057] Example 3

[0058] Platinum sulfite with a mass concentration of 10% and cerium nitrate with a mass concentration of 30% were mixed (the mass ratio of platinum sulfite to cerium nitrate was 1:3) to obtain 300 mL of a mixed solution, and then 15 g of mesoporous titanium dioxide (JK-11-001-100) was added to the mixed solution, and stirring was started at 400 rpm. After stirring for 6 hours, the mixed solution was centrifuged and precipitated, and then the obtained precipitate was dried and calcined, and calcined at 400° C. for 1 hour to obtain a catalytically active component;

[0059] The catalytic active component obtained above was fully ground and mixed with graphite in a mass ratio of 4:1, and then the mixture was dispersed in water, and then the prepared cordierite substrate coated with the high temperature resistant oxide slurry was immersed in the dispersion for 12 hours, and dried after the immersion was completed to obtain a catalyst for catalytic oxidation degradation of chemical tail gas VOCs (the catalytic active component loading was 1.8 g / m 3 ).

[0060] Example 4

[0061] Platinum nitrate with a mass concentration of 20% and cerium nitrate with a mass concentration of 40% were mixed (the mass ratio of platinum nitrate to cerium nitrate was 1:5) to obtain 400 mL of a mixed solution, and then 30 g of mesoporous titanium dioxide (JK-11-001-100) was added to the mixed solution, and stirring was started at 400 rpm. After stirring for 6 hours, the mixed solution was centrifuged and precipitated, and then the obtained precipitate was dried and calcined, and calcined at 350° C. for 2 hours to obtain a catalytically active component;

[0062] The catalytic active component obtained above was fully ground and mixed with graphite in a mass ratio of 5:2, and then the mixture was dispersed in water, and then the prepared cordierite substrate coated with the high temperature resistant oxide slurry was immersed in the dispersion for 10 hours, and dried after the immersion was completed to obtain a catalyst for catalytic oxidation degradation of chemical tail gas VOCs (the catalytic active component loading was 3g / m 3 ).

[0063] Comparative Example 1

[0064] Platinum nitrate with a mass concentration of 15% and lanthanum nitrate with a mass concentration of 30% are mixed (the mass ratio of platinum nitrate to lanthanum nitrate is 1:4) to obtain 500mL of mixed solution, and then graphite is added to the mixed solution for full dispersion (the ratio of the mixed solution to graphite is 500mL:4g). The prepared cordierite substrate coated with high temperature resistant oxide slurry is immersed in the dispersion of the set ratio for 10 hours, and dried after the immersion is completed to obtain a catalyst for catalytic oxidation degradation of chemical tail gas VOCs.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 1 is only that no graphite is added.

[0067] Experimental Example 1

[0068] Evaluation conditions for VOCs degradation reaction: The raw material is chemical tail gas from the process of butane oxidation to maleic anhydride, with a VOCs content of 5000 mg / m 3 , reaction temperature 250℃, gas volume space velocity 40000h -1 , sampling and analysis were carried out after reacting for 1 hour. The VOCs degradation of each embodiment and comparative example is shown in Table 1.

[0069] Table 1 Catalyst degradation effects of Examples 1 to 4 and Comparative Examples 1 to 2

[0070]

[0071] It can be seen from Table 1 that the catalyst prepared by the present invention has excellent catalytic performance, and has excellent degradation effect on chemical tail gas with large emission, high concentration, many types of pollutants and difficult to treat, with the degradation effect reaching more than 99.5%, and the VOCs content after treatment is less than 60mg / m 3 , meeting the relevant emission standards. Comparative Example 1 did not add titanium dioxide, and the degradation efficiency was slightly lower than that of Example 1, because titanium dioxide was also conducive to the catalytic degradation reaction of VOCs. Comparative Example 2 did not add graphite, and the degradation effect was poor, proving that graphite can activate the treated VOCs, reduce the barrier of the catalytic reaction, and improve the catalytic efficiency of the catalyst.

[0072] Experimental Example 2

[0073] The above reaction was continued in Example 1 and Comparative Example 1, and the degradation rates at different use times were recorded.

[0074] Table 2 Degradation efficiency at different treatment times

[0075]

[0076] It can be seen from Table 2 that the catalyst prepared by the present invention has excellent stability, while the degradation efficiency of the catalyst prepared in Comparative Example 1 significantly decreases with the increase of usage time. It is speculated that its active components are easily disturbed and deactivated, thereby affecting the degradation efficiency of the catalyst.

[0077] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0078] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas, characterized in that: The steps include: 1) mixing a noble metal solution, a rare earth salt solution and mesoporous titanium dioxide, separating and calcining the precipitate after the mixing is completed to obtain a catalytically active component; 2) mixing and grinding the catalytically active component and graphite, and then dispersing them in a solvent to obtain a mixed dispersion; 3) The substrate is immersed in the mixed dispersion liquid, and after the immersion is completed, a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas is obtained.

2. The method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas according to claim 1, characterized in that: The mass ratio of the precious metal in the precious metal solution to the rare earth salt in the rare earth salt solution in step 1) is 1:3-5; The noble metal in the noble metal solution includes one or more of a platinum compound, a palladium compound and a ruthenium compound; The rare earth salt in the rare earth salt solution includes one or more of lanthanum salt, praseodymium salt, neodymium salt, cerium salt and yttrium salt.

3. The method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas according to claim 2, characterized in that: The mass concentration of the noble metal solution is 10-20%, and the mass concentration of the rare earth salt solution is 30-40%; The mass ratio of the total volume of the noble metal solution and the rare earth salt solution to the mesoporous titanium dioxide is 30-50 mL: 1-3 g.

4. The method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas according to any one of claims 1 to 3, characterized in that: The mixing time in step 1) is 4 to 6 hours; In step 1), the calcination temperature is 200-400° C. and the calcination time is 1-2 hours.

5. The method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas according to claim 4, characterized in that: The mass ratio of the catalytic active component to graphite in step 2) is 1-5:0.5-2.

6. The method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas according to claim 5, characterized in that: The immersion time in step 3) is 10 to 12 hours.

7. The method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas according to claim 5 or 6, characterized in that: The substrate in step 3) includes one or more of ceramic, cordierite, mullite, silicon carbide and stainless steel coated with a high temperature resistant oxide slurry.

8. The method for preparing a catalyst for catalytic oxidation degradation of VOCs in chemical tail gas according to claim 7, characterized in that: The high temperature resistant oxide slurry includes one or more of an aluminum oxide aqueous solution, a magnesium oxide aqueous solution and a silicon oxide aqueous solution.

9. The catalyst for catalytic oxidation degradation of VOCs in chemical tail gas prepared by the preparation method according to any one of claims 1 to 8.